PEMBUATAN MEDIA PROMOSI BOOKLET COMPANY PROFILE DENGAN MENGGUNAKAN APLIKASI CORELDRAW DI KOPINKA MADIUN - Fath Zulfa Ali; Ahmad Fauzi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Cooperative for INKA’s employee, known as Kopinka, operates in the field of goods and servieces through its business units. Despite promotional activities through social media, Whatsapp groups, discount banners, shooping vouchers, and a company profile, the observations indicate a lack of complete content and less attractive design. This study employs an action research approach using CorelDraw to design the company profile booklet for Kopinka Madiun. Involving 10 units of analysis, including computer experts, marketing experts, company representatives, and consumers, the research result show high average values for the dimensions of empathy, persuasion, impact, and communications. With an Epic rate of 4,5 out of 5, the booklet is considered highly effective, suitable for user, and can be published as an additional promotional media for Kopinka. The research conclusion asserts that the design of the company profile booklet can effectively be utilized as a promotional media in the Cooperative for INKA’s employee.